Relationship between higher estrus-associated temperatures and the bovine preovulatory follicular fluid metabolome - Pollock, Abigayle B.; Moorey, Sarah E.; Hessock, Emma A.; Klabnik, Jessica L.; Payton, Rebecca R.; Schrick, F. Neal; Campagna, Shawn R.; Edwards, J. Lannett (Frontiers in Animal Science, 2023)
Introduction A higher estrus-associated temperature (HEAT) is a hallmark feature in sexually active females; however, its functional importance is unclear. Our objective was to examine the relationship between HEAT and the preovulatory follicular fluid metabolome. It was hypothesized that HEAT is functionally important as it affects fertility-related components in the preovulatory follicle. Methods Estrus was synchronized in non-lactating Jersey cows. A Thermochron iButton temperature data logger was affixed to blank controlled internal drug release (CIDR) devices and intravaginally inserted after CIDR device removal. The follicular fluid was aspirated 14.9 h + 3.3 h after an animal first stood to be mounted. Regression models were performed using metabolite abundance and HEAT variables. Best-fit models were determined using backward manual selection (p < 0.05). Results A total of 86 metabolites were identified in cow follicular fluid samples. The vaginal temperature at first mount and when it was expressed as a change from baseline was positively related to the abundance of four metabolites (i.e., taurine, sn-glycerol 3-phosphate, glycine, and cysteine) and negatively related to one metabolite (i.e., serine). The vaginal temperature at the first standing mount was related to the differential abundance of two metabolites (i.e., jasmonate and N-carbamoyl-L-aspartate). Three metabolites were related to the maximum vaginal temperature (i.e., N-carbamoyl-L-aspartate, uracil, and glycodeoxycholate). When expressed as a change from baseline, the maximum vaginal temperature was related to the differential abundances of uracil, uric acid, and 6-phospho-D-gluconate. The time taken to reach maximum vaginal temperature was related to N-carbamoyl-L-aspartate, glycodeoxycholate, jasmonate, and tricarballylic acid. Pertaining to the combination of HEAT and its duration, the area under the curve associated with the time between the first increase in vaginal temperature and the maximum vaginal temperature was related to 6-phospho-D-gluconate, sulfolactate, guanidoacetic acid, and aspartate. The area under the curve associated with the time between the initial vaginal temperature increase and up to 10 h after a cow first stood to be mounted or when a cow’s temperature returned to baseline was related to the differential abundances of uracil, sn-glycerol 3-phosphate, methionine sulfoxide, and taurodeoxycholate. Discussion Our findings support the notion that HEAT is related to changes in the preovulatory follicular fluid metabolites involved in energy metabolism, thermoregulation, and oxidative stress management.